2022
DOI: 10.3389/fmicb.2021.803031
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Antibodies and Cellular Immune Responses Against SARS-CoV-2 Sustained One and a Half Years After Natural Infection

Abstract: BackgroundCOVID-19 has caused more than 2.6 billion infections and several million deaths since its outbreak 2 years ago. We know very little about the long-term cellular immune responses and the kinetics of neutralizing antibodies (NAbs) to SARS-CoV-2 because it has emerged only recently in the human population.MethodsWe collected blood samples from individuals who were from the first wave of the COVID-19 epidemic in Wuhan between December 30, 2019, and February 24, 2020. We analyzed NAbs to SARS-CoV-2 using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 46 publications
(68 reference statements)
5
13
0
Order By: Relevance
“…The duration of the follow-up regarding the duration of immunity after the SARS-CoV-2 infection is getting increasingly longer: the presence of CD4+ and CD8+ T-lymphocytes has been confirmed over time in subjects recovering from SARS-CoV-2 up to 18 months after infection, as reported among others a few recent publications [53][54][55][56]; furthermore this T-lymphocyte-based immunity was shown to occur regardless of the severity of the clinical picture related to the infection itself [57,58]. Interestingly, no statistically significant differences between the effectiveness of the immune response to natural infection or to the hybrid stimulation (vaccination + natural infection) was documented after about 20 months [33].…”
Section: Cellular Immunitysupporting
confidence: 61%
“…The duration of the follow-up regarding the duration of immunity after the SARS-CoV-2 infection is getting increasingly longer: the presence of CD4+ and CD8+ T-lymphocytes has been confirmed over time in subjects recovering from SARS-CoV-2 up to 18 months after infection, as reported among others a few recent publications [53][54][55][56]; furthermore this T-lymphocyte-based immunity was shown to occur regardless of the severity of the clinical picture related to the infection itself [57,58]. Interestingly, no statistically significant differences between the effectiveness of the immune response to natural infection or to the hybrid stimulation (vaccination + natural infection) was documented after about 20 months [33].…”
Section: Cellular Immunitysupporting
confidence: 61%
“…The duration of the follow-up regarding the duration of the immunity after the SARS-CoV-2 infection is getting increasingly longer: the presence of CD4+ and CD8+ T-lymphocytes has been confirmed over time in subjects recovering from SARS-CoV-2 up to 18 months after infection, as reported in a few recent publications [ 56 , 57 , 58 , 59 ]; furthermore this T-lymphocyte-based immunity was shown to occur regardless of the severity of the clinical picture related to the infection itself [ 60 , 61 ]. Interestingly, no statistically significant differences between the effectiveness of the immune response to natural infection or to the hybrid stimulation (vaccination + natural infection) was documented after about 20 months [ 36 ].…”
Section: Resultsmentioning
confidence: 76%
“…Recently, it was reported that NAbs against SARS-CoV-2 could persist for one and a half years among COVID-19 convalescents 4,39 . However, most of the studies indicated a decreasing trend of the SARS-CoV-2-specific antibody levels with time among the convalescents 1,4 .…”
Section: Discussionmentioning
confidence: 99%